1999
DOI: 10.1093/hmg/8.7.1177
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide difference that alters splicing patterns distinguishes the SMA gene SMN1 from the copy gene SMN2

Abstract: Spinal muscular atrophy (SMA) is a recessive disorder characterized by loss of motor neurons in the spinal cord. It is caused by mutations in the telomeric survival motor neuron 1 ( SMN1 ) gene. Alterations within an almost identical copy gene, the centromeric survival motor neuron 2 ( SMN2 ) gene produce no known phenotypic effect. The exons of the two genes differ by just two nucleotides, neither of which alters the encoded amino acids. At the genomic level, only five nucleotides that differentiate the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
631
0
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 860 publications
(641 citation statements)
references
References 31 publications
2
631
0
8
Order By: Relevance
“…SMA is caused by homozygous deletion or mutation in the SMN1 ( survival motor neuron 1 ) gene and retention of the nearly identical gene, SMN2 ( survival motor neuron 2 ), which results in reduced expression of full‐length SMN protein 3, 4. In humans, SMN2 is present in the same genomic region and differs from SMN1 by a single‐nucleotide substitution that results in the exclusion of exon 7 in approximately 90% of SMN transcripts 5, 6. The mRNA that results, SMNΔ7, produces a truncated protein that is nonfunctional and targeted for degradation 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…SMA is caused by homozygous deletion or mutation in the SMN1 ( survival motor neuron 1 ) gene and retention of the nearly identical gene, SMN2 ( survival motor neuron 2 ), which results in reduced expression of full‐length SMN protein 3, 4. In humans, SMN2 is present in the same genomic region and differs from SMN1 by a single‐nucleotide substitution that results in the exclusion of exon 7 in approximately 90% of SMN transcripts 5, 6. The mRNA that results, SMNΔ7, produces a truncated protein that is nonfunctional and targeted for degradation 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…The SMN2 gene, however, contains a T nucleotide at this position, leading to a differentially spliced form that lacks exon 7 (D7-SMN). 2,[6][7][8] The resulting putative shorter protein has a different C-terminus. It is less stable and cannot oligomerize or self-associate, as occurs with the complete protein.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 80% of SMN2 transcripts exclude exon 7. 16,19 Lorson et al 16 have recently reported that a single nucleotide difference at the sixth nucleotide position in exon 7 (7+6 position) is responsible for the alternative splicing. When the nucleotide is 'C' as in SMN1, exon 7 is recognized and included.…”
Section: Introductionmentioning
confidence: 99%